Characterisation of Myeloid, Lymphiod and Erythroid Cell Lineages in Myelodysplastics Syndrome Using Flow Cytometry - Broojerdi, Mohadese Hashem (2011)
Introduction: Myelodysplastic syndromes (MDSs) are a group of disorders characterised by ineffective haematopoiesis, leading to dysplasia in one, two or all three cell lineages. Although morphological diagnosis is a traditional and the conventional method, method for the diagnosis of MDS, some patients show blood and bone marrow (BM) characteristics that make MDS diagnosis difficult. Flow cytometric immunophenotyping is an accurate and faster method for the detection of abnormalities in different cell lineages. Objective: To determine the expression pattern of antigens in myelomonocytic, lymphoid and erythroid lineages in non-MDS (control group) and MDS, to compare the expression patterns of antigens in myelomonocytic, lymphoid and erythroid lineages in MDS and non-MDS cases, to compare the expression patterns of antigens in myelomonocytic, lymphoid and erythroid lineages in MDS subtypes, and to compare full blood count parameters in MDS and control group in addition between different MDS subtypes. Methods: 30 BM samples from newly-diagnosed MDS patients were analysed by 4-colour FACS Canto flow cytometer (Becton Dickinson,USA) to investigate the antigen expression patterns in granulocytic, monocytic,erythroid and lymphoid lineages and myeloid precursors. The results were compared with those obtained from patients with idiopathic thrombocytopaenic purpura (ITP) (30 samples) as a control. Gating on CD45/SSC (Side Scatter) plot was used for choosing the population of interest. A descriptive analysis was done for all variables studied. Student’s t-test was used for statistical analysis of differences between the MDS and control groups. The one-way ANOVA was used to test of differences between mean percentages of antigens in MDS subtypes. A p-value of ≤ 0.05 was considered as statistically significant. Result: Between full blood count parameters, Hb, Hct, RBC count, WBC count and the ANC were significantly lower in MDS cases. The mean ranges of MCV and platelet count were higher in MDS patients. Between MDS subtypes only the difference of Hct, RBC count and Plt count was statistically significant. The mean percentages of CD33, CD13, CD11b, HLA-DR, CD10 and CD34 positive granulocytes were 91%, 84.98%, 77.20%, 14.59%, 40.34% and 34.25%, respectively, in MDS and 96.89%, 91.57%, 81.47%, 10.56%, 58.30% and 32.37%, respectively, in non-MDS cases. The mean percentage of CD71 (64.54%) was lower in the MDS subtype than non-MDS (83%). In addition, CD235a+ and CD71+/CD235a+erythroid precursors showed lower mean values of 35.96% and 6.61%, respectively, in MDS subtypes, as compared to 52.83% and 10.48%, respectively, in non-MDS cases. The mean proportions of CD14+, CD33+, CD13+, CD34+ and HLA-DR+ monocytes were lower in MDS as compared to non-MDS with values of 65.89%, 79.92%, 74.04%, 44.43%, 36.25% and 73.36%, 86.57%, 87.74%, 45.30%, 38.86%, respectively. Investigation of antigen expression in the myeloid precursors of MDS patients showed mean proportions of: CD117 (19.89%), CD34 (59.53%), HLA-DR (57.26%), CD33 (69.24%), CD13 (60.64%) and CD11b (23.43%). In non-MDS cases the mean percentages of CD117 (11.73%), CD34 45.67%), HLA-DR (58.90%), CD33 (74.28%),CD13 (70.16%) and CD11b (15.66%) were detected. There was no significant difference in lymphoid antigen expression among MDS and non-MDS cases. Between MDS subtypes only the expression pattern of CD71 on erythroid lineage was statistically significant. Discussion: Decrease of CD10+ granulocytes was an important result in this study that had shown by others. Low percentage of CD14+ monocytes and high percentage of HLA-DR+/CD11b+ myeloid precursors were another findings of this study that confirmed immaturity of cells in MDS cases. Erythroid lineage was found by low expression of CD235a+/CD71+, decrease of CD71 and CD235a expression. All results showed cells in MDS patients had lower maturity as compare to cells in non-MDS cases. In addition, our results support the idea that maturity of cells in RAEB subtype is lower than other MDS subtypes. Conclusions: In conclusion, flow cytometric immunophenotyping is useful for confirming cases in which is difficult to determine by morphology, even though the current morphological diagnostic methods are enough to diagnose straightforward MDS cases and are cheaper and more accessible. Key words: Myelodysplastic Syndromes, Flow cytometry, Immunophenotyping;